ادارة المنشأت العامة بين تحديات العولمة وقيود الواقع : في اطار البيئة العربية - طارق شريف يونس (PROSPECTIVE RESEARCHES, 2023)
The main objective of this study is to explain the current situation of public-owned enterprises within the Arab environment. Moreover, the nature of the current limitations which have been confronted is determined. The study identifies the challenges that accompany globalization at the end of the 20th century forming a problematic issue. This issue may lead to widening the developmental gap between North-South regions. It also presents some important dimensions which help to construct Arab models reflecting a global strategy. Finally of restricting of the ongoing comparative advantages of the Arab countries into a competitive advantage and strategic performance criteria leading to strategic output within a globalized framework.